2007
DOI: 10.1001/archpedi.161.12.1154
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Adolescent Self-report of Height and Weight in Assessing Overweight Status

Abstract: Self-reported data are valuable if the only source of data. However, self-reported data underestimate overweight prevalence and there is bias by sex and weight status. Lower sensitivities of self-reported data indicate that one-fourth to one-half of those overweight would be missed. Other potential biases in self-reported data, such as across subgroups, need further clarification. The feasibility of collecting directly measured height and weight data on a state/community level should be explored because direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
322
4
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(378 citation statements)
references
References 20 publications
30
322
4
22
Order By: Relevance
“…Self-reported or parent-reported anthropometrics would have been prone to errors and underreporting (Goodman et al, 2000;Sherry et al, 2007). Many lifestyle-related health behaviors were studied, and therefore, we were able to study the association between many health behaviors and WC or WHtR simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported or parent-reported anthropometrics would have been prone to errors and underreporting (Goodman et al, 2000;Sherry et al, 2007). Many lifestyle-related health behaviors were studied, and therefore, we were able to study the association between many health behaviors and WC or WHtR simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, self-reported data may be all that exist, so it is important to understand when and how such data might be used appropriately. 62 …”
Section: Self-reported Height Weight and Bmimentioning
confidence: 99%
“…64,70,71 A slightly different concern about young adolescents is that they are often unable or decline to report their heights and weights. 62,72 In a study based on US national-level data, 41% of 12-year-olds and 25% of 13-year-olds had missing data for weight. 64 These rates compared with 4% missing reported weights in 15-and 16-year olds.…”
Section: Measurement Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Studies that analyzed weight outcomes also generally relied on self-reported height and weight, which can be misreported. 36 To address these limitations, this longitudinal study was designed to estimate the association between independently coded state laws governing competitive food nutrition content and withinstudent change in BMI and weight status,based onobjectiveheight and weight data collected from adolescents in 40 states. We estimated the association between baseline state laws and student weight change, aswell as the association between changes in state laws over time and student weight change.…”
mentioning
confidence: 99%